Analysis of Curriculum Policy Implementation Freedom to Study at State Vocational High School in Batubara Regency - Muhammad Bahmid Effendi Pulungan; Arif Rahman; Irwandi Irwandi (RIRAI Publisher, 2024)
This research aims to analyze the implementation of the curriculum policy of the Merdeka Study in the State vocational high school of Batu Bara District, concerning Ristek Permendikbud No. 56 Year 2022 and No. 262 Year 2022. The research theory trail uses the framework of Edward III's policy implementation theory. The research method used is descriptive with a qualitative approach. Data was collected through interviews, documentation, and observations, involving respondents consisting of the Head of the Department of Education of Region V, the Head of School, Business Staff, and the State vocational high school Teacher in Batu Bara District. The results of the research show that the implementation of the curriculum policy Merdeka Learning in the State SMC of Batu Bara County is running well, supported by clear communication transmission processes, adequate resources, positive disposal, and an effective bureaucratic structure.